Antecedents And Outcomes Of Psychological Capital: The Role Of Authentic Leadership And Affective Commitment - Marshanda Clarisa Herlambang; Adjeng Mariana Febrianti (Enrichment : Journal of Management, 2022)
This study aims to investigate the relationship between authentic leadership, psychological capital, and affective commitment to teaching staff at three universities located in Bandung, West Java. This research was conducted with quantitative methods, with the determination of the sample using purposive sampling technique. The number of samples in this study were 135 respondents. The data in this study were collected by distributing questionnaires through Google Forms to respondents, as measured by a Likert scale. The results of this study indicate several findings. First, authentic leadership has been shown to have a positive effect on psychological capital and affective commitment. Then, psychological capital is also proven to be able to influence the affective commitment of teaching staff in Bandung City, West Java. This study emphasizes the importance of leadership style in influencing individuals to bring out their positive attitudes at work, which is characterized by psychological capital and affective commitment.